2016
DOI: 10.1186/s13045-016-0261-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in the TCR signaling pathway in patients with aplastic anemia

Abstract: BackgroundA previous study has demonstrated a significantly increased CD3ζ gene expression level in aplastic anemia (AA). However, the mechanism underlying the upregulated CD3ζ mRNA expression level and that of T cell activation signaling molecules in AA patients remains unclear. Thus, we investigated the expression levels of the CD3ζ, CD28, CTLA-4, and Cbl-b genes, the SNP rs231775 in the CTLA-4 gene, and the distribution of the CD3ζ 3′-UTR splice variant in AA patients.MethodsCD3ζ 3′-UTR splice variants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…After the initial denaturation at 95 °C for 2 min, 45 cycles consisting of 95 °C 15 s, 60 °C 60 s and 82 °C 1 s for plate reading were performed using MJ Research DNA Engine Opticon 2 PCR cycler (BIO-RAD, USA). The relative mRNA expression levels of relative gene in each sample were calculated according to the comparative cycle time method [ 17 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…After the initial denaturation at 95 °C for 2 min, 45 cycles consisting of 95 °C 15 s, 60 °C 60 s and 82 °C 1 s for plate reading were performed using MJ Research DNA Engine Opticon 2 PCR cycler (BIO-RAD, USA). The relative mRNA expression levels of relative gene in each sample were calculated according to the comparative cycle time method [ 17 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Results have shown that CD28 promotes Cbl-b degradation, whereas CTLA-4 promotes Cbl-b re-expression (28). An increased CD28 and decreased CTLA-4 and Cbl-b mRNA expression level were also found in patients newly diagnosed with AA (20). These results suggest that aberrant T cell activation in AA not only associates with the initial signals, but it is also related to the secondary signals in the TCR signaling pathway.…”
Section: Cd28 and Ctla-4 And Their Related Factors In Aamentioning
confidence: 80%
“…In most reports, a significant increase in the CD3γ, CD3δ, CD3ε, and CD3ζ expression levels was detected in peripheral blood samples from newly diagnosed AA patients, which may result in enhancing T cell activation (19,20). Interestingly, the CD3ζ expression level was higher in NSAA compared with SAA patients.…”
Section: The Characteristics Of the Cd3 Molecules And Cd3ζ 3'-utr Isomentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, CD8+ T-cells are expanded in AA patients and they show restricted T-cell receptor (TCR) expression[ 13 ]. Some studies suggest that the TCRs themselves show increased expression of CD3-zeta and co-stimulatory molecule CD28 promoting T-cell activation[ 14 ], whereas other studies suggest a restricted TCR with decreased CD3-zeta expression but with aberrant activity[ 15 ].…”
Section: Understanding the Pathogenesis Of Aamentioning
confidence: 99%